Réponses

  • Utilisateur Brainly
2014-09-06T15:07:14+02:00
F(x) = (- x - 1)² + (3 + 2x)(x + 1)
       = x² + 2x + 1 + 3x + 3 + 2x² + 2x
       = 3x² + 7x + 4
merci baucoup
(- x - 1)² = x² + 2x + 1 et non x² - 2x + 1
2014-09-06T15:22:54+02:00
F(x) = (-x - 1 )² + ( 3 + 2 x ) ( x + 1 )
       =  (-x)² - 2 × (-x) × 1 + 1² + 3 × x + 3 × 1 + 2 x × x + 2 x × 1
       =  x² - (-2x)  + 1 + 3 x + 3  + 2 x² + 2 x
       =  x² + 2x + 1 + 3x + 3  + 2 x² + 2x  
       =  x² + 1 + 3  + 2 x² + 2x + 2x + 3x
       = 3x²  + 4 + 7x
       = 3x²  + 7x + 4 
je dois factoriser cette expression et non la développer